2013
DOI: 10.4028/www.scientific.net/amm.347-350.3194
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Optimal Allocation System on the Edible Agricultural Products Components of the Nutrition and Health Care Based on Internet of Things

Abstract: In daily life, the nutrients taken from the food of the human body are often insufficient or surplus, which has a negative impact on human health and waste of agricultural nutrients as well. There is some catering software that can guide people about the intake of the nutrients at home and abroad, but they can only realize the analysis function, that is, tell the user that the nutrients intake is inadequate or exceed the standard. This paper constructs an optimal allocation system of the agricultural products … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Wei et. al [43] found that informatics can guide people in their nutrition intake which prevent them from insufficient and/surplus intake which prevents a negative impact on health. Boulos et.…”
Section: Nutritionmentioning
confidence: 99%
“…Wei et. al [43] found that informatics can guide people in their nutrition intake which prevent them from insufficient and/surplus intake which prevents a negative impact on health. Boulos et.…”
Section: Nutritionmentioning
confidence: 99%